Human Capital Development From Islamic Knowledge Management Perspective - Muhamadul Bakir; Mohd Sofian; Fauzi Hussin; Khatijah Othman (Kulliyyah of Science, International Islamic University Malaysia, 2024)
In the environment of globalization and information boom, the concept of human capital development (HCD) represents the primary concerns of parents, educators, scholars, and leaders. Although the idea is somehow complicated and regarded as very much personal, due to its intangibility embodied within self-functionality and reactivity. In fact, there is no definite answer to the question of how it takes place? For instance, physical capital is a form of material development and applied predominantly in production. While human capital is intangible within the individual acts, conducts and behaviors. In this direction, the purpose of the paper is to develop a hierarchical structure of knowledge management (KM) and Islamic knowledge management (IKM) that aims strategically functioning in developing human capital (HC). The data of this study collected through a brief and random literature review for the purposes of comparison and analysis. The focus was more toward identifying aspects of the relationship values of knowledge, KM, and IKM to the processes of HCD. From the essence of this study, HCD was viewed as essential strategic planning not only to an organizational productivity, but also to an individual personal achievement and societal stability. In other words, the implications of this study covered various statuses of knowledge users.